2023
DOI: 10.1172/jci.insight.168177
|View full text |Cite
|
Sign up to set email alerts
|

An integrated single-cell analysis of human adrenal cortex development

Abstract: The adrenal glands synthesize and release essential steroid hormones such as cortisol and aldosterone, but many aspects of human adrenal gland development are not well understood. Here, we combined single-cell and bulk RNA sequencing, spatial transcriptomics, IHC, and micro-focus computed tomography to investigate key aspects of adrenal development in the first 20 weeks of gestation. We demonstrate rapid adrenal growth and vascularization, with more cell division in the outer definitive zone (DZ). Steroidogeni… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 100 publications
(173 reference statements)
0
0
0
Order By: Relevance
“…Human adrenal cortex development was studied using scRNA-seq, which demonstrated the longitudinal transcriptional changes of diverse cell types included in the developing adrenal gland. In the study, ligand-receptor analysis revealed the potential bidirectional interactions between mesenchyme and adrenal cortex, such as DLK1-NOTCH2 (cortex to mesenchyme) and RSPO3-LGR4 (mesenchyme to cortex) [116]. These techniques have been used in several studies to examine pancreases.…”
Section: Applications Of Scrna-seq and Spatial Transcriptomics In End...mentioning
confidence: 99%
“…Human adrenal cortex development was studied using scRNA-seq, which demonstrated the longitudinal transcriptional changes of diverse cell types included in the developing adrenal gland. In the study, ligand-receptor analysis revealed the potential bidirectional interactions between mesenchyme and adrenal cortex, such as DLK1-NOTCH2 (cortex to mesenchyme) and RSPO3-LGR4 (mesenchyme to cortex) [116]. These techniques have been used in several studies to examine pancreases.…”
Section: Applications Of Scrna-seq and Spatial Transcriptomics In End...mentioning
confidence: 99%